2022
DOI: 10.3390/polym14061095
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies on the Influence of Plasma Treatment of Polyethylene in Carbon Fiber Composites: Mechanical and Morphological Studies

Abstract: This research focused on enhancement of mechanical properties in carbon fiber (CF)-filler-reinforced linear low-density polyethylene (PE) matrix composites. A hand layup method using an oven was used as the fabrication method. Improvement in adhesion was achieved by oxygen plasma treatment to the PE matrix. CF and PE were initially mixed by normal stirring, ultrasonication and mechanical stirring before being filtered and dried for fabrication. Better tensile results were observed with a plasma-treated polyeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Thermoplastic polymers reinforced with high-modulus fibers are multiphase systems that attract more attention from researchers compared to thermosetting-based composites [ 1 , 2 , 3 , 4 ]. Among their numerous advantages are resistance to damage and cracking, ease of consolidation as well as fast and economical manufacturability.…”
Section: Introductionmentioning
confidence: 99%
“…Thermoplastic polymers reinforced with high-modulus fibers are multiphase systems that attract more attention from researchers compared to thermosetting-based composites [ 1 , 2 , 3 , 4 ]. Among their numerous advantages are resistance to damage and cracking, ease of consolidation as well as fast and economical manufacturability.…”
Section: Introductionmentioning
confidence: 99%
“…Te study [13] recommended the green fller material for synthesizing the glass fbre epoxy composite through the compression moulding technique in which the 0.6 wt.% reinforcement outperformed. Te study of [14] investigated the efects of oxygen plasma treatment on polyethylene matrix and found that higher fexural strength of 25.87 MPa was observed by the novel treatment but tensile strength was slightly reduced from 18.2 MPa to 17.7 MPa. Te study [15] used benzoyl chloride treatment for the natural fbres of ramie and kenaf fbres; they optimized the weight percentage of fbres with Taguchi-based grey relational analysis and further optimized by TOPSIS technique [16].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, fiber composites are the most widely used and developed materials. The most recently used fiber-reinforcing agent is carbon fiber (CF), which is mixed with various matrix materials [1][2][3][4][5][6][7][8]. However, these carbon fibers are expensive and have disadvantages.…”
Section: Introductionmentioning
confidence: 99%